THE IMPLEMENTATION OF COOPERATIVE INTEGRATED READING COMPOSITIONON IN READING INTEREST - Donal, Andri; Niati, Batdal (JEE (Journal of English Education), 2017)
To improve students’ reading interest, a comprehensive research was needed.The purpose of this research was to implement Cooperative Integrated Reading Composition(CIRC)on reading interest.This research was quasi experimental research. It was nonequivalent control group design; post-test only design. The treatments were only done in experimental class while control class was taught as usual. Regarding to population selection, total sampling was used. It consisted of two classes. They were thirty nine students. Control class was taught by small group discussion and experimental class was taught by Cooperative Integrated Reading Composition. Reading comprehension test, Questionnaire, and interview were used to collect the data. The data were analyzed by using independent t-test. The finding was students who were taught by cooperativeintegrated reading composition (CIRC) had better scores (comprehension well) thanthose who were taught by small group discussion. However the reading interest of students were still low that can be seen from the time spent for reading and kinds of book read.